Diagnosis of cystic fibrosis in the kindred of an infant with CFTR‐related metabolic syndrome: Importance of follow‐up that includes monitoring sweat chloride concentrations over time. Issue 3 (4th November 2013) - Williams, Sophia N.; Nussbaum, Eliezer; Chin, Terry W.; Do, Paul C.M.; Singh, Kathryn E.; Randhawa, Inderpal
Summary Newly implemented newborn screening (NBS) programs in California have resulted in a large subset of patients in whom at least two cystic fibrosis transmembrane conductance regulator (CFTR) mutations are identified, but subsequent sweat chloride analysis reveals normal or indeterminate values. These patients are diagnosed with CFTR‐Related Metabolic Syndrome (CRMS). However, the natural progression and management of these patients are not clearly understood and frequently after the age of 1‐year these patients are lost to follow‐up with Cystic Fibrosis (CF) Centers. We present the first case of an infant who was referred to Miller Children's Hospital for a NBS positive for CF and subsequent discovery of identical mutations in six of his seven older brothers. Several siblings had positive sweat chloride results on repeat testing after the age of 3 years. We suggest the need for continued follow‐up of CRMS in a CF center with diagnostic evaluation including repeat sweat chloride testing, beyond the currently recommended period. Pediatr Pulmonol. 2014; 49:E103–E108. © 2013 Wiley Periodicals, Inc.